Deficiency for MicroRNA-582 does not impact dilated cardiomyopathy or heart failure induced by pressure overload in vivo - Martini, Simone; Dobberstein, Inka; Schmiedel, Nesrin; Kilian, Lucia Sophie; Voran, Jakob Christoph; Senger, Frauke; Rangrez, Ashraf Yusuf; Frank, Derk; Kuhn, Christian; Frey, Norbert (Frontiers in Cell and Developmental Biology, 2025)
MicroRNAs (miRNAs) are critical post-transcriptional regulators of gene expression and have been extensively implicated in cardiovascular development, homeostasis, and disease. Among them, microRNA-582 (miR-582) has been associated with several non-cardiac pathologies, yet its role in the heart remains poorly characterized despite significant cardiac expression. In this study, we investigated the functional significance of miR-582 in cardiac pathophysiology through both gain- and loss-of-function approaches. We observed differential expression of miR-582 in murine models of cardiomyopathy, prompting further mechanistic evaluation. Thus, we generated transgenic mice with cardiac-specific overexpression of miR-582 (TG-582) as well as miR-582 knockout (582-KO) mice. Neither model exhibited an obvious cardiac phenotype under basal conditions. Following pressure overload via transverse aortic constriction (TAC), both TG-582 and 582-KO mice developed hypertrophy and functional adaptations comparable to wildtype controls. Additionally, crossbreeding these models with Calsarcin-1-knockout (CS1-KO) mice, a model of dilated cardiomyopathy, did not modify the pathological phenotype. These results indicate that miR-582 does not play a determinative role in pressure overload-induced cardiac hypertrophy or in the progression of dilated cardiomyopathy. Our findings highlight the importance of rigorously controlled in vivo studies to accurately define the cardiac miRNA landscape and to guide future therapeutic strategies.